KOMUNIKASI INTERPERSONAL DALAM PEMBELAJARAN AGAMA HINDU DI SEKOLAH MENENGAH PERTAMA NEGERI 8 MATARAM - I Nyoman Subudiartha (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2015)
Create a learning environment that is naturally necessary to have good communication among students and between students and teachers, while the form of communication is to encourage students to make connections with the knowledge application in their lives as members of the family and community with the application process carried out naturally, for example, to communicate and sit together in the practice of making cymbals as a means of Hindu religious ceremonies, with the concept, the learning outcomes expected to be more meaningful for students. In contextual barriers often faced is not communicative students sitting together in these activities, generally they busy themselves with the means of communication that they carry, such as HP, IPAD and IPHONE, although the rules at school are already rules ban, though given sanction , students still repeating his actions. The reality of what happened above reminds us that, the education we've done so far has not been able to achieve the objectives (outcomes) effectively and efficiently. With the implementation of interpersonal communication in the learning Hinduism in SMP Negeri 8 Mataram, is expected to provide improved quality, process and the outcome.The problem formulated in this study is how the interpersonal communication in teaching Hinduism in Junior High School 8 Mataram and any obstacles encountered during the implementation of interpersonal communication in teaching Hinduism in Junior High School 8 Mataram theory used in this study is a communication theory of Edgar Dale, theories of learning and motivation theory. This study uses a sociological approach, which examines on social interactions that occur in the learning process Hinduism in SMP Negeri 8 Mataram, both among students, teachers and the surrounding community.While this research is a qualitative research, this research means emphasis on the quality of the research object, the interpersonal communication in teaching Hinduism in SMP Negeri 8 Mataram. In conclusion, namely interpersonal communication in teaching Hinduism in Junior High School 8 Mataram, namely: 1) Teacher Hinduism in Junior High School 8 Mataram are applying interpersonal communication management in Learning Hinduism to improve the quality of learning, with steps activities as follows: initial activity, core activities and events end the learning process, 2) School of Hinduism emphasizes the application of learning to use interpersonal communication in the classroom, so that it is used in the application of communication theory, theories of learning and motivation theory as the process of formation of students' knowledge, thus students are actively engaged in thinking, draft and give meaning about the things that are being studied. Underlying interpersonal communication in the classroom learning the Hindu religion are as follows: Production of messages, message processing, coordination and perception of social interaction. Obstacles encountered during the implementation of learning management Interpersonal communication Hinduism in Junior High School 8 Mataram is due to appear on the student's internal factors such as: 1) motivation interinsik weak students and 2) students are less cooperative and avoid responsibility. While external factors occur due to: lack of support for parents of children and teachers still carry traditional learning, whereas in contextual learning the teacher should have to have an open nature, and can help students become open, can cooperate in order to power sharing and can act as facilitators in the learning activities.